The resealing factor S100A11 interacts with annexins and extended synaptotagmin-1 in the course of plasma membrane wound repair - Ashraf, Arsila P. K.; Gerke, Volker (Frontiers in Cell and Developmental Biology, 2022)
After damage, cells repair their plasma membrane in an active process that is driven by Ca2+ entering through the wound. This triggers a range of Ca2+-regulated events such as the translocation of different Ca2+-binding proteins to the wound site which likely function in the repair process. The translocated proteins include Ca2+/phospholipid binding proteins of the annexin (ANX) family and S100A11, an EF hand-type Ca2+-binding protein which can interact with ANX. The molecular mechanism by which S100A11 mediates PM wound repair remains poorly understood although it likely involves interactions with ANX. Here, using S100A11 knockout endothelial cells and expression of S100A11 mutants, we show that endothelial S100A11 is essential for efficient plasma membrane wound repair and engages in Ca2+-dependent interactions with ANXA1 and ANXA2 through its C-terminal extension (residues 93-105). ANXA2 but not ANXA1 translocation to the wound is substantially inhibited in the absence of S100A11; however, the repair defect in S100A11 knockout cells is rescued by ectopic expression of an ANX interaction-defective S100A11 mutant, suggesting an ANX-independent role of S100A11 in membrane wound repair. In search for other interaction partners that could mediate this action of S100A11 we identify extended synaptotagmin 1 (E-Syt1), a protein tether that regulates endoplasmic reticulum-plasma membrane contact sites. E-Syt1 binds to S100A11 in the presence of Ca2+ and depletion of E-Syt1 interferes with wound site recruitment of S100A11 and proper membrane resealing. Thus, the role of S100A11 in membrane wound repair does not exclusively dependent on ANX interactions and a Ca2+-regulated S100A11-E-Syt1 complex acts as a yet unrecognized component of the membrane resealing machinery.